PEMANFAATAN NAUNGAN DAN PUPUK KOTORAN SAPI TERHADAP PERTUMBUHAN DAN KANDUNGAN TRITERPENOID PEGAGAN (Centella asiatica L.) - Mustika Tripatmasari; Catur Wasonowati; Vidya R. Alianti (Universitas Trunojoyo Madura, 2010)
Gotu kola (Centella asiatica L.) is one of the medicinal plants widespread in the tropics and subtropics. Gotu kola plant has long been used as traditional medicine to cure various diseases. One of the chemical constituent beneficial to this plant Centella asiatica is triterpenoids. The Objective of this research is to observe the effect of shade and cow manure on growth and triterpenoid content of gotu kola. The research was arranged using Split Plot Design with 2 replications. Main plot is shading level consists ie without shade (0%) and shade of 30%. The subplot was the dosages of cow manure that is, without fertilizer, 20 tons/ha and 30 tons/ha. Components of growth and production observed at 4 plant selected of each plot treatment. Observations of growth include the number of leaves, number of stolon, petiole length per plant was observed at 14, 28, 42, 56, 70, 84, 98, 112 and 124 days after transplanting (DAT) and production components include leaf area, fresh weight, dry weight and content of triterpenoids were observed the end of the study (124 HST). The results showed there is interaction of shading level and cow manure with different doses on the number of leaves at the age of 84 HST observations (the highest value N0P0 = 609 leaves), stolon number of observations at age 14, 42, 56, 70, and 84 HST ( The highest value N1P0 = 49 stems), petiole length at the age of 70 HST observations (the highest value N0P0 = 14.8 cm), leaf area at the age of 124 HST observations (N1P2 = 3.92 cm2), the content of triterpenoids at the age of 124 HST observations (the highest value N0P2 = 18.00 mg / kg), but have no effect on the wet weight and dry weight. Treatment combinations reduced number of stolon and leaves, but increased stem length and leaf area compared with control. Dosages of 30 tons / ha cow manure fertilizer gave a higher fresh weight than the other treatments.